In praise of Asclepius : selected prose hymns - Aristides, Aelius; Brockmann, Christian; Melfi, Milena; Nesselrath, Heinz-Günther, 1957-; Parker, Robert, 1950-; Russell, D. A. (Donald Andrew); Steger, Florian, 1974-; Trapp, Michael B. (Sapere (Darmstadt, Germany), 2016)
In the second century AD Aelius Aristides wrote eight prose hymns to Greek gods. This volume presents a new edition of the Greek text of four of these hymns (focusing on Asclepius), a new English translation with notes, and a number of essays shedding additional light on these texts from various perspectives.